Salary, flexibility or career opportunity? A choice experiment on gender specific job preferences - Jost, Madlaina; Möser, Sara (Frontiers in Sociology, 2023)
Using the evaluation of hypothetical job offers in a discrete choice experiment, we analyse which characteristics of employment positions are relevant to men and women when deciding between job offers. Thereby, we investigate whether preferences for work arrangements are gender-specific. The analysis shows that on average, women have a stronger preference for part-time work than men, and that the career prospect of a job is more important to men than to women. Furthermore, we use heterogeneity within genders to study whether gender-specific preference patterns result from gendered considerations of family formation. We find that certain men and women, especially those who plan to have children and have traditional expectations about the division of labour in the household, evaluate work relationships more strongly according to gendered roles than others. This analysis of hypothetical employment choices provides valuable insight into the preference structure of men and women, which proves to be heterogeneous within and between genders.